Tight correlation of 5-hydroxymethylcytosine expression with the scarring damage of discoid lupus erythematosus. (October 2022) - Li, Qianwen; Yang, Ming; Chen, Kaili; Zhou, Suqing; Zhou, Shengnan; Wu, Haijing
Objective: Cutaneous lupus erythematosus (CLE) is a heterogenous skin disease. The two most common subtypes are discoid LE (DLE) characterized by scarring skin damage and acute CLE (ACLE) presenting with transiently reversible skin lesions. It remains unknown what causes the difference of skin lesions. Studies have shown the existence of tissue-specific 5-Hydroxymethylcytosine (5 hmC)-modified regions in human tissues, which may affect the tissue-related diseases. Here, we aim to assess the expression of 5 hmc in DLE and ACLE lesions and explore the relationship of 5 hmc with scarring damage in DLE. Methods: 84 CLE samples were included in the study. We evaluated the skin damage score and reviewed the histopathologic sections. Immunohistochemical staining was performed to detect the expression of 5 hmc in the appendage and periappendageal inflammatory cells. The 5 hmc expression in periappendageal lymphocytic cells was investigated by multi-spectrum immunohistochemistry staining. Results: Scarring/atrophy was the most significant damage in differentiating the DLE from ACLE. Perifollicular inflammatory infiltration was present in all patients with DLE scarring alopecia (DLESA). The 5 hmc expression in the appendage and periappendageal inflammatory cells was significantxly increased in DLESA than ACLE. Similar expression pattern was seen in the staining of IFN-alpha/beta Receptor (IFNAR). The expression of 5 hmc in the appendage was positively correlated with that in the periappendageal inflammatory cells. There was an increased 5 hmc expression in lymphocytes cluster around hair follicle consisting of CD4 + cells, CD8 + cells, and CD19 + cells in DLESA lesions. Conclusion: These data demonstrate a close association of the expression pattern of 5 hmc with the histopathological characteristic distribution, and with the type I interferons (IFNs) signals in DLESA, supporting the importance of 5 hmc in the amplification of appendage damage and periappendageal inflammation, thereby offering a novel insight into the scarring damage of DLE and the heterogeneity of CLE skin lesions.